Avaliação da interação por rastreamento de cabeça em computador e tablet - MURAKAMI, Bruno Akira Fukuchima (2020)
This work has the objective to study and evaluate head tracking (HT) interactions in Desktop and Mobile applications. The chosen applications for the evaluation were: file manager and web browser because they are applications used daily and frequently by the users. The HT is based in a low-cost technology, both software and hardware, free software and a common webcam. The evaluation of the interaction through HT aims the click and double click, both considered low-level interactions, and usability tests with users. Therefore, 10 tasks were defined for desktop computer environment, divided into 5 for the file manager and 5 for the web browser. As for the mobile platform (tablet), 7 tasks were defined, 4 for file manager and 3 for the web browser, being that for each platform involved 10 users. In turn, the qualitative aspect made use of the Thinking-aloud Protocol to extract user information about his experience with HT. Finally, the results indicate that the users feel more uncomfortable when they perform interactions in the corners of the screen independent of the platform and tracking is more accurate in the desktop environment than on the tablet, as well the icons are considered small by the users.